A Paradigm Shift for a More Inclusive, Equal, and Just Academia? Towards a Transformative-Emancipatory Pedagogy - Teresa Maria Cappiali (MDPI AG, 2023)
This article puts forward the core argument that a pedagogical shift is very much needed if we want to address the challenges and capitalize on the opportunities represented by increasingly diverse educational settings and move towards a more inclusive, equal, and just academia. First, it is suggested that we replace the current pedagogical models in use, namely, the teacher-centered and student-centered models, as their educational philosophies are insufficient and can be considered, to a certain extent, oppressive. Then, it is argued that transformative pedagogy can broaden the scope of academic goals by including students' well-being, as well as their individual and collective emancipatory goals. To support the argument, the author presents a theoretical framework that has been developed over time while teaching migration topics to students coming from all over the world. The framework includes a holistic approach rooted in transformative pedagogy, which engages with students' cognitive, practical, and affective dimensions. It is further argued that the theoretical framework should integrate intersectional and decolonial approaches into its praxis. These approaches offer further insights into how to challenge power imbalances in the classroom, center the experiences and voices of marginalized communities, and recognize the interplay between individual experiences, systemic oppressions, and the broader socio-political context. The article concludes by explaining that transformative pedagogy has not yet received the attention it deserves, both in practice and in research, and that more efforts need to be made to explore its potential and scientific relevance.